2021
DOI: 10.1002/rsa.20992
|View full text |Cite
|
Sign up to set email alerts
|

Phase transitions of Best‐of‐two and Best‐of‐three on stochastic block models

Abstract: This paper is concerned with voting processes on graphs where each vertex holds one of two different opinions. In particular, we study the Best-of-two and the Best-of-three. Here at each synchronous and discrete time step, each vertex updates its opinion to match the majority among the opinions of two random neighbors and itself (the Best-of-two) or the opinions of three random neighbors (the Best-of-three). Previous studies have explored these processes on complete graphs and expander graphs, but we understan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…w.h.p., where C > 0 is a constant depending only on f . In Corollary 1.8(i), we stress that the worst-case consensus time on G(n, p) was known for p = Ω(1) [39].…”
Section: Our Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…w.h.p., where C > 0 is a constant depending only on f . In Corollary 1.8(i), we stress that the worst-case consensus time on G(n, p) was known for p = Ω(1) [39].…”
Section: Our Resultsmentioning
confidence: 99%
“…Doerr, Goldberg, Minder, Sauerwald, and Scheideler [21] showed that, on the complete graph K n , the consensus time of best-of-two is O(log n) with high probability 1 for an arbitrary initial opinion configuration. Since best-of-two is simple and is faster than pull voting on the complete graphs, this model gathers special attention in distributed computing and related area [26,15,16,17,19,20,39]. There is a line of works that study best-of-two on expander graphs [15,16,17], which we discuss later.…”
Section: Previous Work Of Specific Updating Rulesmentioning
confidence: 99%
See 2 more Smart Citations
“…From a high level perspective, our results show that adding a bias to k-majority affects the dynamics in a non-trivial way. In particular, the arise of a metastable phase makes the framework suitable to design distributed algorithms to recover planted partitions in networks [CNS19,BCPR19,SS19]. In this direction, we discuss potential applications of the mathematical framework presented in this paper in Section 7.…”
Section: Our Contributionmentioning
confidence: 99%